Design and fabrication of innovation of goods sanitizer / Muhammad Faeez Haikhal Mohd Fuad and Zeno Michael - Mohd Fuad, Muhammad Faeez; Michael, Zeno (School of Mechanical Engineering, 2022)
Nowadays, sanitising goods is crucial and required especially in this pandemic era. Iit will prevent us from being infected by Corona Virus. The number of cases of people that have been infected with this virus today has drastically increased. Some of them were infected by touching unsensitized goods. So, a new innovative design of goods sanitizer will be fabricated so that it will help to reduce the number of infections. The product objective is to reduce the number of infections that occur, either intentionally or indirectly, contacting other persons. It can prevent us from spreading the virus to other people. Thus, the infection can be reduced every day. An innovation has been made to this product with the installation of both air purifier and air humidifier. The idea is to maintain the existing product function and combine both systems to a new product design